Pharmacogenetics: Influence of CYP2C9*2 and *3 alleles polymorphisms on Iraqi type 2 diabetic patients - Ghada S. Rasool; Asmaa A. Hussien; Suhad R. Al-Tayie; Salwa J. Al-Awadi; Hussein OM Al-Dahmoshi (Medical Journal of Babylon, 2024)
Abstract Background: Sulfonylureas (SUs) are the most prescribed anti-diabetic drugs. The enzyme responsible for metabolizing of SUs is hepatic cytochrome P4502C9 (CYP2C9). The CYP2C9 gene has numerous allelic variations; among those, the CYP2C9*2 and CYP2C9*3 are the most common and clinically significant allelic variations. The pharmacokinetics of SUs are dramatically impacted by CYP2C9 genotype. Objective: Evaluation of the association of genetic polymorphisms in CYP2C9 gene with the efficacy of glibenclamide (GB), second-generation SUs, by investigating two CYP2C9 allelic variants. Materials and Methods: Blood samples were collected from 113 type 2 diabetes patients. Allele specific amplification-polymerase chain reaction was used to genotype the CYP2C9 gene. Fasting serum glucose, fasting insulin, and glycated hemoglobin (HbA1c) levels were measured as part of the biochemical analysis. Results: The CYP2C9 gene variants were analyzed in a study group. The results exposed that 75 patients carried the wild (CYP2C9*1/*1) genotype, 25 were heterozygote allele (CYP2C9*1/*2) for CYP2C9*2 gene, 4 were homozygous for the variant CYP2C9*2 allele (CYP2C9*2/*2), and 9 were heterozygous for the variant CYP2C9*3 allele (CYP2C9*1/*3). Statistically significant difference was found in mean HbA1c between the mutant and wild alleles group (P = 0.044). The mean HbA1c for those carrying the CYP2C9*2 and*3 alleles (n = 38) was 8.4750 compared to 9.3177 for those carrying the CYP2C9*1 allele (n = 75), which indicate better glycemic control. Conclusion: The accordance of CYP2C9*2 and*3 was found to be associated with severe hypoglycemia (odd ratio [OR] = 2.045). The OR suggests a strong association between CYP2C9*2 and*3 alleles and hypoglycemia. Our findings imply that the diabetic patients with CYP2C9 polymorphism are more likely to suffer hypoglycemia than those with wild type alleles when treated with GB.